Experience from Research on Indoor and Outdoor Air Quality in the Poznań Agglomeration - Małgorzata Basińska; Michał Michałkiewicz (Atmosphere)
This article explores how the location of a building in an urban area, the level of external air pollution, and the way a residence is used can affect indoor air quality. To assess this, this study used measurements of physical and chemical pollutants, as well as microbiological measurements, including counts of various bacteria and microscopic fungi. These included counts of mesophilic and psychrophilic bacteria, mannitol-positive and mannitol-negative Staphylococcus, Actinobacteria, Pseudomonas fluorescens, and microscopic fungi. The research involved analysing indoor and outdoor air quality in 38 selected spaces within buildings in the city of Poznań during the heating season. The study found that the eastern part of the city showed the highest levels of fungal contamination in the external environment. Furthermore, distinct differences were observed between the presence of microorganisms indoors and outdoors based on the results of bacterial and fungal aerosol studies. The authors advocate for including microbiological studies as part of standard air quality assessment indicators to reveal the extent and source of contamination, as similar issues may be present in cities around the world.